2019
DOI: 10.1667/rr15243.1
|View full text |Cite
|
Sign up to set email alerts
|

Automated Triage Radiation Biodosimetry: Integrating Imaging Flow Cytometry with High-Throughput Robotics to Perform the Cytokinesis-Block Micronucleus Assay

Abstract: The cytokinesis-block micronucleus (CBMN) assay has become a fully-validated and standardized method for radiation biodosimetry. The assay is typically performed using microscopy, which is labor intensive, time consuming and impractical after a large-scale radiological/nuclear event. Imaging flow cytometry (IFC), which combines the statistical power of traditional flow cytometry with the sensitivity and specificity of microscopy, has been recently used to perform the CBMN assay. Since this technology is capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
49
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
3
2

Relationship

5
3

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 30 publications
0
49
0
Order By: Relevance
“…Moreover, our protocols for RABiT-II cell harvesting with the use of centrifuge [9,15,17] as well as described in this paper centrifuge-free RABiT-II approach were developed for keeping all reagents and plates at room temperature so that more workstations without automated heaters/coolers could be used for CBMN assay sample preparation. Thus, almost any ANSI/SLAC-format compatible robotic cell handling system meeting the minimum requirements of the centrifuge-free RABiT-II approach can be used for sample preparation with the use of the corresponding RABiT-II systems has the potential to increase the capacity for biodosimetry response during a large-scale radiological/nuclear event.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, our protocols for RABiT-II cell harvesting with the use of centrifuge [9,15,17] as well as described in this paper centrifuge-free RABiT-II approach were developed for keeping all reagents and plates at room temperature so that more workstations without automated heaters/coolers could be used for CBMN assay sample preparation. Thus, almost any ANSI/SLAC-format compatible robotic cell handling system meeting the minimum requirements of the centrifuge-free RABiT-II approach can be used for sample preparation with the use of the corresponding RABiT-II systems has the potential to increase the capacity for biodosimetry response during a large-scale radiological/nuclear event.…”
Section: Discussionmentioning
confidence: 99%
“…Fresh blood aliquots (1 mL) were dispensed into 15 mL conical bottom tubes (Santa Cruz Biotechnology, Dallas, TX) and were irradiated with γ rays (0, and 4 Gy) using a Gammacell ® 40 137 Cesium irradiator (Atomic Energy of Canada, Ltd., Chalk River, ON). The blood sample tubes were placed on their side in the middle of the chamber and irradiated with a dose rate of 0.73 Gy/min (35). The 137 Cs irradiator was calibrated annually with TLDs and homogeneity of exposure across the sample volume was verified using EBT3 Gafchromic film with less than 2% variation within the sample (Ashland Advanced Materials, Gafchromic, Bridgewater, NJ).…”
Section: Methodsmentioning
confidence: 99%
“…partial-body photon exposures, or vs. neutron + photon mixtures. Specifically, using our highthroughput CBMN assay 5,9,46 we wish to evaluate on an individual basis: 1) the photon and the neutron doses and the fraction of neutrons in the total dose after a mixed exposure, 2) whether there was indeed a partial body exposure. Our study design (shown schematically in Fig.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, there are a larger number of undamaged cells than would be expected based on Poisson statistics, coupled with more damage in those that are traversed by ionizing tracks. While these phenomena has been observed for many years and applied to the dicentric assay, essentially by analyzing the proportion of undamaged metaphases [33][34][35] , these approaches can be directly applied to high-throughput assays 5,6 .…”
Section: Current Approaches For Evaluating Complex Exposuresmentioning
confidence: 99%
See 1 more Smart Citation